(3TQM bUjOg GdfGHZI GdPHjGfi (B( (3GdOGdjI (B)s - (3CHh GdMSf Ydj Hf CMeO Hf Ydj Hf efhjg GdhGMOi GdfjSCHhQis
(3ChdgG (B:s
(3jGOGQ ejg HGdYdjG aGdSfO CbQJ aWGd YdjgG SGda GdCHO s
(3BNQgG (B:s
(3gPG GdPi PcQJ YRQi aEf de jfaYfi JMjQJ hde GgJO dhLg JeJ GdbUjOI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HBNQ UaMGJgG JYbjHIs
(3JJab ai ChdgG hBNQgG eY GdfSNI GdChdis
(3HGNJdGa ai HYV GdCdaGXs
(3fSNI QGHYg s
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs